Pelatihan Penerjemahan dan Pembuatan Takarir Inggris-Indonesia bagi Guru dan Siswa SMAN 2 Purwokerto - Aditya, Aldi; Prayogo Hadi Sulistio; Usep Muttaqin; Nadia Gitya Yulianita (BEMAS: Jurnal Bermasyarakat, 2022)
People now have access to a broader and more diverse selection of audiovisual shows thanks to Era 4.0. As a result, the demand for watching and translating audiovisual shows in foreign languages (in this case, English) into Indonesian or other local languages is increasing. Thus, the goal of this project is to provide subtitle translation training to students and teachers at SMAN 2 Purwokerto in Central Java, who have the potential to learn translation media well because they have language classes and a film club. It is believed that this activity will help students and teachers at SMAN 2 Purwokerto develop their interests and expertise in the field of translation, particularly subtitle translation, which will be very useful in their professional lives.